Analisis Faktor-Faktor yang Memengaruhi Nilai Tukar Petani Kedelai di Desa Nglebur, Kecamatan Kedungpring, Kabupaten Lamongan - tiara, Irma; Mubarokah; Itasa, Dita (Universitas Medan Area, 2024)
The welfare of farmers can be known through the amount of Farmer Exchange Value obtained. This research was conducted with the aim of analyzing the average exchange rate for soybean farmers and the factors that influence it in Nglebur Village, Kedungpring District, Lamongan Regency. The research location was selected purposively using secondary data and primary data from 76 farmer respondents. The data analysis used is Farmer Exchange Rate Analysis and Multiple Linear Regression Analysis. This analysis shows that the average exchange rate for soybean farmers in Nglebur Village is 118%, meaning that soybean farmers are quite prosperous. The results of the analysis show that the factors that have a significant influence on the Farmer's Exchange Rate are Land Area, Production Costs, Selling Prices, Production Amount, Food Expenditures and Non-Food Expenditures. Meanwhile, farmer age, farmer education and number of family dependents do not have a significant effect on the exchange rate for soybean farmers in Nglebur Village.